2018
DOI: 10.1155/2018/7967694
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Solid Extraction for Simultaneous Determination of Eleven Commonly Used Anticancer Drugs and One Active Metabolite in Human Plasma by HPLC-MS/MS

Abstract: Therapeutic drug monitoring for anticancer drugs could timely reflect in vivo drug exposure, and it was a powerful tool for adjusting and maintaining drug concentration into a reasonable range, so that an enhanced efficacy and declined adverse reactions could be achieved. A liquid chromatography-tandem mass spectrometry method had been developed and fully validated for simultaneous determination of paclitaxel, docetaxel, vinblastine, vinorelbine, pemetrexed, carboplatin, etoposide, cyclophosphamide, ifosfamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In order to ensure the accuracy, reliability, and stability of the determination results, the precision and accuracy, extraction recovery and matrix effect, stability, and specificity of this method should meet the requirements of biological sample analysis. Methodological verification was conducted in accordance with the Chinese pharmacopeia (version 2015) and FDA guidelines, and the experiments were carried out as we reported previously [14,15]. ), the results showed that the pemetrexed and IS had better peak shapes and responses on Zorbax SB-C 18 chromatographic column and could achieve complete separation from the internal interferent substances in a short time.…”
Section: Methodological Studymentioning
confidence: 99%
“…In order to ensure the accuracy, reliability, and stability of the determination results, the precision and accuracy, extraction recovery and matrix effect, stability, and specificity of this method should meet the requirements of biological sample analysis. Methodological verification was conducted in accordance with the Chinese pharmacopeia (version 2015) and FDA guidelines, and the experiments were carried out as we reported previously [14,15]. ), the results showed that the pemetrexed and IS had better peak shapes and responses on Zorbax SB-C 18 chromatographic column and could achieve complete separation from the internal interferent substances in a short time.…”
Section: Methodological Studymentioning
confidence: 99%
“…Majority of the LC–MS/MS methods (Bai et al, ; Canal‐Raffin et al, ; de Jonge et al, ; DiFrancesco, Griggs, Donnelly, & Robert DiCenzo, ; Ekhart et al, ; Gao et al, ; Shu et al, , ; Zhou et al, ) quantified CP and its metabolites from patient samples used in clinical studies. A simple protein precipitation enabled the quantification of CP and its metabolites by HPLC coupled with electrospray ionization coupled to MS (ESI‐MS/MS) using acetonitrile and methanol mixture as an extraction solvent with an LLOQ of 200 and 50 ng/mL for CP and 4‐OHPC, respectively (de Jonge et al, ; Ekhart et al, ).…”
Section: Case Studiesmentioning
confidence: 99%
“…Majority of the LC-MS/MS methods (Bai et al, 2009;Canal-Raffin et al, 2016;de Jonge et al, 2004;DiFrancesco, Griggs, Donnelly, & Robert DiCenzo, 2007;Ekhart et al, 2007;Gao et al, 2018;Shu et al, 2011Shu et al, , 2016Zhou et al, 2012) The LLOQ was 1 ng/mL for CP or fludarabine (Silvertand et al, 2005).…”
Section: -Ohcp Is Highly Unstable In Biological Matrices and Rapidlymentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been reported in the literature for the estimation of ETO, MOX and NAL in their pharmaceutical dosage form and/or biological fluids; for ETO: spectrophotometric [8], spectrofluorimetric (SF) [9], electrochemical [10,11], high-performance thin-layer chromatography (HPTLC) [12], high-performance liquid chromatography (HPLC) [13][14][15][16][17], gas chromatography (GC) [18] and capillary electrophoresis (CP) [19]; for MOX: spectrophotometric [20,21], SF [22], electrochemical [23], HPTLC [24], HPLC [25][26][27] and CP [28] and for NAL spectrophotometric [29][30][31], SF [31,32], flow injection analysis [33,34], HPLC [35][36][37] and GC [38]. These presented methods did not guide the monitoring of these three drugs in the biological matrices.…”
Section: Introductionmentioning
confidence: 99%